“It’s Just ‘Locker Room’ Talk”: The Impact of Gender and Political Partisanship on Agreement with Rape Myths Among US University Students - Hansen, Michael (Victims & offenders, 2025)
Allegations of sexual assault against prominent politicians have led to highly partisan debates. Studies demonstrate that alongside gender, partisanship has become a powerful predictor of views on the #MeToo movement and sexual assault, but this empirical inquiry has not yet been assessed across the attitudes of rape myths among university students. The main research question in this study is, “To what extent is rape myth acceptance among university students a product of gender and political partisanship?” We surveyed around 1,000 university students and asked their level of agreement with two constructs of rape myths: that women are to blame for rape and that women lie about rape. Several findings stand out. First, Democratic and Republican men express statistically the same level of rape myth acceptance. Second, there exists a sizable partisan gap among women in levels of rape myth acceptance, with Democratic women conveying stronger disagreement with rape myths than Republican women. Third, the partisan gap in rape myth acceptance is driven by the difference between Democratic and Republican women, with Democratic women driving the gender gap.